Palbociclib Negatively Regulates Fatty Acid Synthesis Due to Upregulation of AMPK Alpha and miR-33a Levels to Increase Apoptosis in Panc-1 and MiaPaCa-2 Cells - RENCÜZOĞULLARI, ÖZGE; YERLİKAYA, PINAR OBAKAN; GÜRKAN, AJDA ÇOKER; Telci, Dilek; ARISAN, ELİF DAMLA (Wiley, 2022)
Fatty acids (FAs) synthesis mechanism has various regulators such as fatty acid synthase (FASN), AMP-regulated protein kinase (AMPK), or mammalian target of rapamycin (mTOR), which are aberrantly dysregulated in various pancreatic cancer cells. In this study, we aim to understand the regulatory role of palbociclib, a CDK4/6 inhibitor, on the cellular energy metabolism through regulation of AMPK/mTOR signaling by modulation of intracellular miR-33a levels in Panc-1 and MiaPaCa-2 cells. Palbociclib downregulated FAs metabolism more effectively in MiaPaCa-2 cells than Panc-1 cells. Moreover, palbociclib treatment increased the levels of miR-33a in each cell line albeit a higher increase was evident in MiaPaCa-2 cells. Stress-mediated activation of mTOR signaling axis was found associated with palbociclib-mediated AMPK alpha activation and miR33a upregulation. These findings provided that a deeper understanding about possible interactions of cell cycle activity and reduction of FAs synthesis may facilitate the enhancement of cell death mechanisms in pancreatic cancer cells.
Keywords: AMPKα; Fatty Acid Synthesis; Leptin; miR-33a; Palbociclib; Pancreatic Cancer